Bifurcation Analysis in a Delayed Diffusive Leslie-Gower Model - Shuling Yan; Xinze Lian; Weiming Wang; Youbin Wang (Discrete Dynamics in Nature and Society)
We investigate a modified delayed Leslie-Gower model under homogeneous Neumann boundary conditions. We give the stability analysis of the equilibria of the model and show the existence of Hopf bifurcation at the positive equilibrium under some conditions. Furthermore, we investigate the stability and direction of bifurcating periodic orbits by using normal form theorem and the center manifold theorem.